2020
DOI: 10.20527/jstk.v14i2.8330
|View full text |Cite
|
Sign up to set email alerts
|

EKSTRAKSI GLUKOMANAN DARI TEPUNG PORANG (Amorphophallus muelleri Blume) DENGAN ETANOL

Abstract: Iles-Iles kuning (Amorphophallus muelleri Blume) adalah sumber potensial glukomanan, suatu senyawa polisakarida yang memiliki beberapa sifat khusus yang sering digunakan di berbagai bidang industri, farmasi, dan makanan. Kualitas glukomanan yang diproduksi di dalam negeri masih belum dapat menyamai kualitas glukomanan impor. Penelitian ini bertujuan untuk mengetahui pengaruh perbedaan metode ekstraksi glukomanan dari tepung iles-iles kuning menggunakan etanol untuk mendapatkan kadar glukomanan yang tinggi deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
2
5
1
10
Order By: Relevance
“…In terms of calcium oxalate removal, treatment S was found as the most effective one as indicated by the lowest value of calcium. Overall, the result followed the treatments in that the sodium residue were higher in B, S, and BS samples compared to that of C and W samples, whereas the calcium residues of C and W samples were higher than that of B, S, and BS samples (Nurlela & Arizal, 2020;Rofi'ana et al, 2018;Witoyo et al, 2020). Therefore, EDS analysis can be used to evaluate the presence of calcium oxalate in the Amorphophallus flour sample.…”
Section: Eds Analysis Of Samplesmentioning
confidence: 89%
See 2 more Smart Citations
“…In terms of calcium oxalate removal, treatment S was found as the most effective one as indicated by the lowest value of calcium. Overall, the result followed the treatments in that the sodium residue were higher in B, S, and BS samples compared to that of C and W samples, whereas the calcium residues of C and W samples were higher than that of B, S, and BS samples (Nurlela & Arizal, 2020;Rofi'ana et al, 2018;Witoyo et al, 2020). Therefore, EDS analysis can be used to evaluate the presence of calcium oxalate in the Amorphophallus flour sample.…”
Section: Eds Analysis Of Samplesmentioning
confidence: 89%
“…The result of this experiment showed that the identity peak of oxalate in four different Amorphophallus flour samples including the C=O group appeared at 1610 cm -1 and the peak C-O was observed at 1322 cm -1 (Figure 1). Nurlela & Arizal (2020) reported that the C=O groups in the glucomannan structure (Figure 2) show two identity peaks at a wavenumber 1739 cm -1 and 1736 cm -1 . Nurlela & Arizal (2020) also noted that the presence of the C-O group was seen at a wavenumber of 1230 cm -1 and 1247 cm -1 .…”
Section: Ftir Spectra Of Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Metode kimiawi menggunakan pelarut etanol atau air untuk mengekstrak glukomanan dari tepung konjac glukomanan. Penelitian isolasi glukomanan dari umbi talas dan iles-iles telah dilakukan berdasarkan atas daya kelarutan glukomanan pada konsentrasi etanol secara bertingkat (60-80%) dan gaya sentrifugal untuk memisahkan pati dari glukomanan, dapat menghasilkan glukomanan dengan kemurnian sebesar 90% (Nurlela et al, 2020).…”
Section: Pendahuluanunclassified
“…Analisis gugus fungsi menunjukkan sampel bulbil yang diesktraksi memiliki kemiripan spektrum terhadap glukomanan komersil. Porang merupakan sumber karbohidrat tinggi karena kandungan glukomanan yang terdapat pada bagian umbi (Nurlela et al, 2020). Selain pada bagian umbi, glukomanan juga dapat ditemukan pada bagian bulbil atau umbi daun.…”
Section: Info Artikel Abstrakunclassified